ACCURACY LEVEL OF CAPM AND APT MODELS IN DETERMINING THE EXPECTED RETURN OF STOCK LISTED ON LQ45 INDEX - Yunita, Irni; Gustyana, Tieka Tri Kartika; Kurniawan, Dwi (Jurnal Aplikasi Manajemen, 2020)
This study determines the accuracy level of CAPM and APT in determining the expected return of LQ45 and comparing the expected return from CAPM and APT models. This study uses descriptive and comparative research approaches. The population is all stocks listed in the LQ45 index while the sampling method used is purposive sampling with stock criteria that have complete data for the period November 2015 - November 2019. This study uses an independent sample t-test in testing the expected return differences between the CAPM and APT models. The result showed that the CAPM Model was more accurate in determining the expected return of LQ45 stocks compared to the CAPM method. The result also showed that there was a significant difference in expected return between CAPM and APT models. Based on this result, investors can use the CAPM model in predicting the returns of the stock listed on the LQ45. For further research, can use another index in the capital market as a research object, used a longer period to get a more accurate result, and add some more macro variables.